Influence of water in the MQL technique in the grinding of steel AISI 4340 using CBN wheels - Sato,Bruno Kenta (2018)
Abstract Usually, machining employs cooling methods to avoid high temperatures. In most cases, the cutting fluid is applied with high flow and low pressures. This technique consumes a large amount of cutting fluid that causes serious problems in the environment and in the health of the worker. An alternative to the conventional cooling method is the Minimum Quantity of Lubricant. The MQL attempts to minimize the consumption of cutting fluid, which this study is about, whereby the reduction provided by this MQL was 99.99%. This technique consumes only the necessary quantity of cutting fluid to create a thin film of lubricant on the cutting surface grinding wheel. The MQL aerosol is injected with high pressure in the contact zone, efficiently lubricating the grinding process. However, the cooling effect of MQL is not enough to dissipate all heat produced during the grinding process. This study analyzes the improvement in the cooling effect caused by the addition of water in the MQL. The tests were done using different concentrations of cutting fluid in water, e.g. 1:0, 1:1, 1:3, 1:5 (oil:water). The experiment occurred on the external cylindrical plunge grinding with a vitrified cubic boron nitrite (CBN) grinding wheel, serving as the workpiece, the AISI 4340 quenched and tempered steel. The analyzed outputs were: surface roughness, roundness deviation, acoustic emission and vibration.. The results improved with the addition of water in the cutting fluid used in the MQL technique. The comparison with the MQL conditions showed that the best condition was the fluid with more water concentration.